Survey of root canal irrigating solutions used in dental practices within Germany. (16th September 2014) - Willershausen, I.; Wolf, T. G.; Schmidtmann, I.; Berger, C.; Ehlers, V.; Willershausen, B.; Briseño, B.
Abstract Aim Irrigant usage information in relation to years of professional experience was collected from general dentists in different German federal states by means of a questionnaire. Methodology A short survey concerning endodontic treatment and use of irrigants was mailed to 4240 dentists or delivered to 3720 dental offices as an extra page in a journal in eight German states. Detailed information concerning the most frequently used irrigants, their concentrations, the spectrum of disinfectants used in root canal treatment concepts for vital and nonvital pulps, main topics of continuing education as well as years of professional experience was collected. The statistical analysis of differences found amongst the dentists in relation to professional experience or federal state was performed using the chi‐square test. Results Of a total of 7960 invitations, 1630 replies were evaluated (response rate 20.5%). The majority of the dentists (57.3%) had >20 years of professional experience, 23% had >30 years. Dentists with long‐standing professional experience (20–30 years) used H2O2 significantly more often than dentists with less experience (P < 0.001), and of the older colleagues (>30 years of professional experience), 14.6% never used NaOCl, whilst the younger colleagues almost always used it (P < 0.001). Differences were also found for the usage of irrigants amongst dentists from the various German states. Conclusions Whilst NaOCl was used in almost all states, regional differences were found regarding the choice of additional irrigants, which were mainly determined by the irrigation protocols taught at different universities.